Assessment of Internet Service Quality on Campus and Its Impact on Student Satisfaction - Ahmad Faris Al Faridzin; Andi Muhammad Nur Hidayat (Jurnal Media Informasi Teknologi, 2026)
Internet service quality plays an important role in supporting digital-based academic activities in higher education, including online learning, access to scientific journals, and academic communication. However, students still frequently experience network problems such as slow and unstable connections, high latency, jitter, and packet loss, which may affect the effectiveness of the learning process. This study aims to evaluate the quality of campus internet services based on Quality of Service (QoS) parameters and analyze their relationship with student satisfaction toward campus internet services. The study employed a quantitative approach using observation and survey methods. QoS measurements were conducted using Speedtest and Pingtest at several campus locations during peak and non-peak hours, while student satisfaction data were collected through an online survey involving 120 respondents. The data were analyzed using descriptive analysis and Pearson correlation analysis. The results showed that internet network quality decreased during peak hours, indicated by lower internet speed and higher latency, jitter, and packet loss. The survey results also revealed that most students were still dissatisfied with the quality of campus internet services. Correlation analysis indicated that internet speed had a positive relationship with student satisfaction, while latency, jitter, and packet loss had negative relationships with user satisfaction levels. Based on the findings, increasing bandwidth capacity, adding Wi-Fi access points, and conducting regular network maintenance are necessary to improve the quality of campus internet services.